The Role of Talent for Entrepreneurs - Sjaiful, Evilina (Journal of Multi-Disciplines Science, 2023)
Talent needs to be a concern for every Entrepreneur. Talented entrepreneurs have the potential to contribute to creating a welfare state. This study aims to identify the role of Talent for Entrepreneurs. This study uses a qualitative method using literature and descriptive studies. The results of this study have explained the definition of entrepreneurial Talent, the role of Talent for entrepreneurs, and Talent as a driver of entrepreneurial success. This study found three roles of Talent for Entrepreneurs: Talent influences interest in entrepreneurship, Talent can make someone competent and successful in running Entrepreneurs, and Talent represents the best people for work in an entity and who will significantly contribute to achieving its strategic goals. Government and educational institutions must identify human resources with the right Talents to become entrepreneurs.